PENGARUH KETERBUKAAN PERDAGANGAN, INVESTASI, INFLASI, DAN ANGKATAN KERJA TERHADAP PERTUMBUHAN EKONOMI PADA DELAPAN NEGARA ASEAN PERIODE 2008-2015 - Ilmiddina Afifah; Firman Rosjadi Djoemadi; Mintarti Ariani (Perpustakaan Universitas Surabaya, 2018)
The economic growth of 8 ASEAN countries is influenced by various factors. The main purpose of this research is to analyze the influence of Trade Openness, Investment, Inflation, and Labor Force to Economic Growth of 8 ASEAN countries for period 2008-2015. To prove the research hypothesis used model of econometric with method of OLS (Ordinary Least Square), estimated by using Eviews version 6. From result of analysis can be concluded that the variables of Trade Openness, Investment, Inflation and Labor Force based on result of test simultaneously, all variables simultaneously have a significant affect to Economic Growth of 8 ASEAN countries at a significance level of 5% with a probability of 0.000020. While individually, the variable of Trade Openness has positive and insignificant effect on Economic Growth with coefficient 0.010085. Investment variable has negative and insignificant effect on economic growth with coefficient of -0.079034. Inflation variable and Labor Force variable have positive and significant influence to Economic Growth with each coefficient of 0.142221 and 2.032047.